2017
DOI: 10.1103/physrevd.96.124018
|View full text |Cite
|
Sign up to set email alerts
|

Critical phenomena and chemical potential of a charged AdS black hole

Abstract: We study the thermodynamics and the chemical potential for a five-dimensional charged AdS black hole by treating the cosmological constant as the number of colors N in the boundary gauge theory and its conjugate quantity as the associated chemical potential µ. It is found that there exists a small-large black hole phase transition. The critical phenomena are investigated in the N 2 -µ chart. In particular, in the reduced parameter space, all the thermodynamic quantities can be rescaled with the black hole char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…This result is also the same as that of Ref. [65]. In addition, we have another exponent (1 −P ) = 0.1142 × |1 −Ṽ | 1.9058 , for coexistence small black hole, 0.2318 × |1 −Ṽ | 2.0954 , for coexistence large black hole.…”
Section: Critical Exponentssupporting
confidence: 89%
“…This result is also the same as that of Ref. [65]. In addition, we have another exponent (1 −P ) = 0.1142 × |1 −Ṽ | 1.9058 , for coexistence small black hole, 0.2318 × |1 −Ṽ | 2.0954 , for coexistence large black hole.…”
Section: Critical Exponentssupporting
confidence: 89%
“…In literature, the critical phenomenon and the phase transition of several AdS black holes in various gravitational setups have already been explored. The first order phase transition for five dimensional charged AdS black holes was investigated in [8]. Similar critical behavior was also observed for the AdS black hole in massive gravity [9].…”
Section: Introductionsupporting
confidence: 57%
“…Taking the temperature and fluid density as parameter space variables, the Ruppeiner scalar curvature, plotted as a function of pressure for fixed temperature was found to have two divergent points and a self-crossing behaviour. This behaviour was later observed in other black hole systems [21][22][23]. Although it was suggested that similar self-crossing behaviour can be used to determine the phase transition point [24] for normal hydrogen (or even a black hole), this idea is still speculative.…”
mentioning
confidence: 88%